A literature review of forgiveness as a beneficial intervention to increase relationship satisfaction in couples therapy. Issue 1 (2nd January 2016) - Aalgaard, Ross A.; Bolen, Rebecca M.; Nugent, William R.
ABSTRACT: Forgiveness between couples is identified as a strong predictor of relationship satisfaction. Yet forgiveness is often overlooked as a potential intervention to help couples increase their relational satisfaction. The purpose of this literature review is to examine the use of forgiveness as a therapeutic intervention to increase relational satisfaction for opposite- and same-sex couple dyads. Forgiveness is also introduced as an effective component of marital interventions in the context of infidelity. Specific areas that are addressed within this article include forgiving personalities, which benefits stress and health, forgiveness affecting marital and family functioning, forgiveness and relationship satisfaction with mediating mechanisms, and limitations of forgiveness interventions. Recommendations for practice are offered.